The relationship between gut microbiota and proteolytic activity in irritable bowel syndrome. (August 2021) - Hou, Jun-Jie; Wang, Xin; Li, Ying; Su, Shuai; Wang, Yu-Ming; Wang, Bang-Mao
Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disease that affects 3.8–9.2% of the world population. It affects the physiology and psychology of patients and increases the burden on families, the healthcare system, society, and economic development. Presently, a large number of studies have shown that compared to healthy individuals, the composition and diversity of gut microbiota in IBS patients have changed, and the proteolytic activity (PA) in fecal supernatant and colonic mucosa of IBS patients has also increased. These findings indicate that the imbalance of intestinal microecology and intestinal protein hydrolysis is closely related to IBS. Furthermore, the intestinal flora is a key substance that regulates the PA and is associated with IBS. The current review described the intestinal microecology and intestinal proteolytic activity of patients with IBS and also discussed the effect of intestinal flora on PA. In summary, this study proposed a pivotal role of gut microbiota and PA in IBS, respectively, and provided an in-depth insight into the diagnosis and treatment targets of IBS as well as the formulation of new treatment strategies for other digestive diseases and protease-related diseases. Highlights: The microecology is altered in IBS, in this case, the microbiota is closely related to the incidence and severity of IBS. The PA in the fecal supernatant and colonic mucosa of patients with IBS is increased. Gut microbiota produces both proteases and protease inhibitors, which proves the ability of the flora to regulate PA. New diagnosis and treatment strategies should be developed for IBS, as well as protease-related diseases.